ANALISIS KINERJA PERMODALAN KOPERASI LEMBAGA EKONOMI MASYARAKAT BADAN USAHA MILIK DESA KARANGLO TAWANGMANGU KABUPATEN KARANGANYAR - Alvian Sri Hermawan, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2019)
The purpose of this study was to determine the level of performance of the Capital Cooperative of the Community Economic Institution (LEM) of Village-Owned Enterprises (BUMDes) Karanglo, Tawangmangu District, viewed from the aspect of capital which includes the capital ratio of capital to capital and capital adequacy ratio (CAR) and aspects of cooperative identity. Which includes the Member Economic Promotion ratio (PEA), and the gross participation ratio. The scope of this research is Village Owned Enterprises in Karanglo Village, Tawangmangu District, which is engaged in Cooperatives and has a financial report of at least 5 periods since 2013 - 2017. The source of this research data uses secondary data in the form of a RAT obtained from the BUMDes of Karanglo village in the Tawangmangu sub-district. The data analysis technique used for this study uses quantitative descriptive analysis method, where this method analyzes the collected data then the data is processed using ratio analysis. Financial ratios are numbers obtained from the comparison results of one financial statement post with other posts that have a relevant and significant relationship. Based on the results of the discussions that have been conducted show the results that the ratio of equity to cooperative total capital is included in the healthy criteria, capital adequacy ratio ( CAR) cooperatives enter the criteria is quite healthy, the ratio of gross participation of cooperative cooperatives in Karanglo village is included in the criteria, and the ratio of economic promotion of members (PEA), the glue cooperative of Karanglo village is included in the beneficial criteria. Keywords: Cooperatives, Financial Statements, Capital Performance